The interactive effects of perceived peer drinking and personality profiles on adolescent drinking: a prospective cohort study - Pocuca, N.; Hides, L.; Quinn, C.; White, M.; Mewton, L.; Newton, N.; Slade, T.; Chapman, C.; Teesson, M.; Andrews, G.; Allsop, Steve; McBride, Nyanda (Wiley-Blackwell Publishing Ltd., 2018)
Aims: (1) To classify Australian adolescents according to their alcohol consumption trajectories; and (2) to assess the direct and interactive effects of perceived peer drinking (PPD) and personality on adolescent drinking. Design: Prospective cohort study comprising secondary analysis of six waves of prospective data (collected between 2014 and 2016) from the control arm of the Climate Schools Combined Study. Setting: Nineteen schools across three Australian states. Participants: A total of 1492 socio-demographically diverse students (mean age at baseline: 13.47; 68% female; 82% born in Australia). Measurements: Alcohol consumption trajectories were assessed using self-reported sipping of alcohol, full standard drink consumption, binge drinking and quantity and frequency of alcohol consumption. One item assessed PPD and personality was assessed using the Substance Use Risk Profile Scale. Findings: Eight hundred and sixty-four (58%) adolescents consumed alcohol across the study period. Four drinking trajectories were identified: abstaining (n = 513; reference group); onset (n = 361; initiated after baseline); persistent (n = 531; initiated prior to baseline); and decreasing (n = 50; consumed alcohol at baseline but ceased or decreased thereafter). A significant PPD × anxiety sensitivity (AS) interaction affected probability of belonging to the onset (P < 0.001) and persistent (P = 0.003) trajectories. The effect of PPD on probability of belonging to the onset trajectory was only significant when adolescents reported low [95% confidence interval (CI) = 1.464–2.646, P < 0.001], but not high AS. The effect of PPD on probability of belonging to the persistent drinking trajectory was stronger at low (95% CI = 2.144–3.283, P < 0.001), compared with high (95% CI = 1.440–2.308, P < 0.001) AS. Conclusions: In Australian adolescents, self-reported drinking onset and persistent drinking appear to be more strongly associated with perceived peer drinking in those with low anxiety sensitivity than those with high anxiety sensitivity.